Quantifying the resuspension of nutrients and sediment by demersal trawling. (15th January 2022) - Breimann, Sarah A.; O'Neill, Finbarr G.; Summerbell, Keith; Mayor, Daniel J.
Abstract: Demersal fisheries trawling is widely acknowledged as one of the most intense forms of widespread benthic disturbance, resuspending extensive plumes of sediments and dissolved nutrients. However, difficulties associated with sampling within trawl plumes have hitherto limited our quantitative understanding of these widespread phenomena. This lack of knowledge hinders our ability to understand the broader consequences of demersal trawling and the development of new fishing gears to limit benthic disturbance. Here we present data from a series of novel in situ experiments using a specially designed trawl sled to quantitatively examine how trawl gear-induced drag and pressure influence the height and concentrations of resuspended sediments and nutrients within a trawl plume. Our data demonstrate that the composition of resuspended particles and sampled nutrients are both influenced by sampling height above the seafloor and the amount of drag exerted by the trawl gear (p < 0.001 in all cases), although the relative importance of these factors differed between the response variables examined. These differences likely reflect that sediment particles are more influenced by gravity than dissolved nutrients are. Our results demonstrate that trawl gear specification strongly influences the amount of dissolved and particulate material resuspended, suggesting that their design could be modified to reduce impacts on benthic ecosystems. Highlights: PSDs were driven by hydrodynamic processes such as turbulent shearing and the pressure drop in the gear wake. Low-drag gear components resuspended lower concentrations of nutrients from the sea floor to the water column. Nutrient concentrations increased as weight-induced pressure on the seabed was increased. Concentrations of particle-associated nutrients changed with height from the seafloor. Combined PSD and nutrient data indicated that higher nitrate and nitrite concentrations were associated with high-drag trawls. Combined PSD and nutrient data indicated that higher phosphate and silicate concentrations were associated with finer particles. Smaller, low drag trawl components reduce the concentrations and height to which material is resuspended.